Sociopatas digitais: comportamento antissocial e empatia em ambientes virtuais - Assis Junior, Fabio de Paula (2017)
The tools that emerge within digital tracking can assume positive usages, as much as negative ones, reminds Lucia Santaella in “Ecologia Pluralista da Comunicação: Conectividade, Mobilidade, Ubiquidade” (2010). Fernanda Bruno, on the other hand, in “Máquinas de Ver, Modos de Ser: Vigilância, Tecnologia e Subjetividade” (2013), alleges that tracked communication steps in the construction of contemporary man subjective identity, both for good and for evil. Nevertheless, what evil is ithis? How this alleged evil operates within digital universe? For answering this questions, it is necessary to understand evil from a philosophical point of view, in order to understand the complexity that this concept assumes within the moral - this, in turn, inserted in time and space limits. Hannah Arendt, in “Eichmann em Jerusalém - Um relato sobre a banalidade do mal” (1999) points to two kinds of malignancy: the banal evil, unplanned, brought on by ordinary people in everyday situations; and a supreme evil, planned, that derives from gaining advantages and power for an individual or group of people, precisely from the manipulation commonly associated with feelings usual to most human beings, especially empathy, shame and fear. This pattern of behavior coincides, according to Ana Beatriz Barbosa Silva in “Mentes Perigosas: o Psicopata Mora ao Lado” (2008), with the profile understood by psychiatry as the antisocial personality disorder, also called sociopathy. Understanding how the sociopath acts in the digital universe is thus the subject of this research. In the virtual medium - where ubiquity determines human behavior - empathy, fear and shame of an individual can be used to obtain advantages by another individual and also by groups of individuals, both in the private sphere and in the public domain. Does the sociopath find a fertile territory in the social media to act to others detriment? Which are the negative usages that can be made from digital communication? How can data tracking tools be used for evil? But, if the network is a complex system as dynamic as the physical universe, what is the role that the sociopath fulfills in the digital universe? How does it work in this complex system? Identifying and qualitatively typifying their actions organizes information and opens paths to answering those questions. Bullying, trolling, copy cat, hackerism, gaslighting and mind control are some of the types already consecrated, and deserve to be tabulated. All these actions, in some of their stages, run counter to the realm of tracking. Even more: what are the flanks in the internet that fit antisocial behavior? Establishing this limit, by typifying the actions of sociopaths in the social media, and characteristics of digital empathy and alterity, can foster a digital morality. And, finally, add knowledge to the forensic sciences, combating digital crimes, besides expanding the studies and debates about the meaning of evil and promoting ethics on communication in digital mediums